Supporting family caregivers to identify their own needs in end-of-life care: Qualitative findings from a stepped wedge cluster trial - Aoun, Samar; Deas, Kathy; Toye, Christine; Ewing, G.; Grande, G.; Stajduhar, K. (SAGE Publications Ltd, 2015)
Introduction: The Carer Support Needs Assessment Tool encompasses the physical, psychological, social, practical, financial, and spiritual support needs that government policies in many countries emphasize should be assessed and addressed for family caregivers during end-of-life care. Aim: To describe the experience of family caregivers of terminally ill people of the Carer Support Needs Assessment Tool intervention in home-based palliative care. Methods: This study was conducted during 20122014 in Silver Chain Hospice Care Service in Western Australia. This article reports on one part of a three-part evaluation of a stepped wedge cluster trial. All 233 family caregivers receiving the Carer Support Needs Assessment Tool intervention provided feedback on their experiences via brief end-of-trial semi-structured telephone interviews. Data were subjected to a thematic analysis. Results: The overwhelming majority reported finding the Carer Support Needs Assessment Tool assessment process straightforward and easy. Four key themes were identified: (1) the practicality and usefulness of the systematic assessment; (2) emotional responses to caregiver reflection; (3) validation, reassurance, and empowerment; and (4) accessing support and how this was experienced. Conclusion: Family caregivers appreciated the value of the Carer Support Needs Assessment Tool intervention in engaging them in conversations about their needs, priorities, and solutions. The Carer Support Needs Assessment Tool presented a simple, yet potentially effective intervention to help palliative care providers systematically assess and address family caregivers needs. The Carer Support Needs Assessment Tool provided a formal structure to facilitate discussions with family caregivers to enable needs to be addressed. Such discussions can also inform an evidence base for the ongoing development of services for family caregivers, ensuring that new or improved services are designed to meet the explicit needs of family caregivers.